The Role of Psychological Empowerment in Achieving Employees Happiness: An Empirical Study - Elsawy, Mahmoud; Ali, Mohamed (The Arab Journal of Administration, 2024)
The current study aims to investigate the relationship between the psychological empowerment and employees Happiness. A random sample of 242 Employees was chosen from the governmental health sector in Ajman. In addition to investigating the statistical significance differences between employees’ feelings (psychological empowerment - Happiness) according to the sample demographic variables. A questionnaire has been used to collect the primary data, the results showed that there are statistical significance differences between employees’ feelings (psychological empowerment - Happiness) according to the sample demographic variables, the results also revealed that there is a significant positive relationship between (psychological empowerment - Happiness). The researchers have also come up with a set of recommendations.